The Antecedent and Consequence of Youth Drug Abusers’ Life Satisfaction: Delinquency Behavior as the Mediator - Mohamad, Mahadzirah; Mohammad, Morliyati; Salleh, Fauzilah; Ghani, Mazuri Abd; Ramli, Rafazila; Afthanorhan, Asyraf (Journal of Reviews on Global Economics, 2019)
The incidents of drug-abuse behavior has escalated especially among youths in Malaysia. The objectives of the study were to ascertain the effects of social support on drug abuse through life satisfaction. Delinquency was treated as the mediating factor on the relationship between life satisfaction and drug-abuse behavior. A survey was conducted among youth addicts getting treatment at rehabilitation centers. A total of 275 questionnaires were analyzed using Structural Equation Modelling. Findings revealed that social support had a significant influence on life satisfaction. Delinquency had a full mediating effect on the relationship between life satisfaction and drug abuse. An increase in life satisfaction would reduce delinquency and drug-abuse behavior among youth by enhancing social support assistance. Therefore, rehabilitation programs should be focused on matching the drug dependences’ needs for social support to increase the chances of remaining sober and achieving success in ending the cycle of relapse.